2009
DOI: 10.1002/jcb.22268
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of rRNA synthesis and ppUL83 nucleolar compartmentalization on human cytomegalovirus gene expression in vitro

Abstract: The nucleolus is a nuclear domain involved in the biogenesis of ribosomes, as well as in many other important cellular regulatory activities, such as cell cycle control and mRNA processing. Many viruses, including herpesviruses, are known to exploit the nucleolar compartment during their replication cycle. In a previous study, we demonstrated the preferential targeting and accumulation of the human cytomegalovirus (HCMV) UL83 phosphoprotein (pp65) to the nucleolar compartment and, in particular, to the nucleol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Consistent with previous reports of their separate localizations (3,4,27), immunofluorescent analysis revealed that IFI16 and pUL83 were colocalized within the nucleus and nucleolus in infected cells at 48 hpi following infection at a low multiplicity of infection (Fig. 5A).…”
Section: Resultssupporting
confidence: 92%
“…Consistent with previous reports of their separate localizations (3,4,27), immunofluorescent analysis revealed that IFI16 and pUL83 were colocalized within the nucleus and nucleolus in infected cells at 48 hpi following infection at a low multiplicity of infection (Fig. 5A).…”
Section: Resultssupporting
confidence: 92%
“…In this experiment, MRC5 fibroblasts enriched in G1, G1/S, S, and G2/M were infected with HCMV for 3 h and then double‐labeled (nucleolar proteins: green; pp65: red) by indirect IF. The expected accumulation of pp65 within the nucleolar compartment [Arcangeletti et al, 2003, 2009] was only evident in G1‐ and G1/S‐synchronized cells, while this pattern was either faintly observable in some cells (most likely cells still residing in G1) or absent in S and G2/M, where the viral protein was almost evenly distributed over the whole nucleus. It should be recalled that pp65 belongs to the “early‐late” group of HCMV‐encoded proteins; the expression of this protein does not start at 3 h p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning HCMV, the association of specific viral components with different nuclear domains has been demonstrated [Sanchez et al, 1998; Ahn and Hawyard, 2000; Lee et al, 2004; Lymberopoulos and Pearson, 2007; Salsman et al, 2008]. In particular, our group has described accumulation in nucleoli of the major tegument protein pp65 of the incoming HCMV at very early stages of infection, also showing that a functional relationship is likely to exist between the nucleolar localization of pp65 and the correct development of HCMV lytic cycle [Arcangeletti et al, 2003, 2009]. In this respect, it is of importance that the nucleolus is involved in the control of the cell cycle in mammalian cells [Boisvert et al, 2007] also through its role in the biogenesis of ribosomes [Ruggero and Pandolfi, 2003; Pliss et al, 2005].…”
mentioning
confidence: 99%
“…How this occurs is unclear, but a direct interaction with nucleolin would provide a simple explanation. Alternatively, it has been reported that several viral proteins, including pp65, can localize to the nucleolus during infection (32)(33)(34)(35). UL84 and pp65 have been reported to interact within the infected cell (16), and thus, pp65 may recruit UL84 to the nucleolus or vice versa, or other viral or cellular factors may be involved.…”
Section: Discussionmentioning
confidence: 99%